CURCUMIN – EXTRACTION, SYNTHESIS AND APPLICATION IN MODERN DRUG RESEARCH: A MINI REVIEW (International Journal of Food and Nutritional Sciences, 2022)
The rhizome of the Curcuma longa is known to contain curcumin, demethoxycurcumin, and bisdemethoxycurcumin, three naturally occurring yellow pigments belonging to the curcuminoid family. Curcuminoids and all its derivatives are active components in many nutraceuticals and cosmetic products. The therapeutic benefits of curcumin are exhaustive and have been proven by numerous scientific investigations. This mini review aims to delveinto the various methods of extraction and isolation of curcumin along with its synthetic route. In addition, the various biological activities, like the antioxidant and antibacterial characteristics, of curcumin are also discussed.